FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PENCEGAHAN PENULARAN HUMAN IMMUNODEFICIENCY VIRUS (HIV) OLEH IBU RUMAH TANGGA DI NGANJUK, JAWA TIMUR - Chahya Kharin Herbawani; Dadan Erwandi (Puslitbang Upaya Kesehatan Masyarakat, 2019)
Abstract Background: HIV/AIDS reports show an increasing number of AIDS cases and the cumulative number of AIDS among housewives at first rank. Objective: to determine factors related to HIV/AIDS prevention efforts for housewives in the Bagor Health Center area. Method: Quantitative research with cross-sectional design. Independent variable; age; education; family income; age at first sexual intercourse; knowledge of HIV/AIDS; risk perception; husband's work; history of VCT; access to condoms and information about HIV/AIDS. The dependent variable is HIV/AIDS prevention efforts. Total respondent were 150 housewives, data collection using a questionnaire that was adopted/modified from the Integrated Biological and Behavioral Surveillance questionnaire (STBP) 2011. Multivariate data analysis with multiple logistic regression Results: Factors related to HIV/AIDS prevention efforts in housewives were a history of VCT (p=0.028) and exposure to information about HIV/AIDS (p=0.014). History of VCT is the most influencing factor in HIV/AIDS prevention efforts in housewives (p value=0.040; OR=3.79 95% CI=1.06-13.537). Housewives who have done VCT are 3.79 times more likely to make HIV/AIDS prevention efforts than those who did not. Conclusion: Providing education and VCT testing can provide better HIV prevention behavior for housewives. Historical factors of VCT and information exposure play a role in HIV prevention behavior in housewives Key words: HIV/AIDS, reproductive health, VCT Abstrak Latar belakang: Laporan HIV/AIDS menunjukkan peningkatan jumlah kasus AIDS dan jumlah kumulatif AIDS pada ibu rumah tangga yang menempati urutan pertama Tujuan: mengetahui faktor-faktor yang berhubungan dengan upaya pencegahan HIV/AIDS pada ibu rumah tangga di wilayah Puskesmas Bagor. Metode: Penelitian kuantitatif dengan desain cross-sectional. Variabel independen; umur; pendidikan; penghasilan keluarga; umur pertama kali berhubungan seksual; pengetahuan HIV/AIDS; persepsi berisiko; pekerjaan suami; riwayat VCT; akses terhadap kondom dan keterpaparan informasi tentang HIV/AIDS. Variabel dependen adalah upaya pencegahan HIV/AIDS. Responden berjumlah 150 ibu rumah tangga, Pengumpulan data menggunakan kuesioner yang diadopsi/dimodifikasi dari kuesioner Surveilans Terpadu Biologis dan Perilaku (STBP) Tahun 2011. Analisis data multivariate dengan multiple logistic regression Hasil: Faktor yang berhubungan dengan upaya pencegahan HIV/AIDS pada ibu rumah tangga adalah riwayat VCT (p=0,028) dan keterpaparan informasi tentang HIV/AIDS (p=0,014). Riwayat VCT merupakan faktor paling mempengaruhi upaya pencegahan HIV/AIDS pada ibu rumah tangga (p value=0,040; OR=3,79 95% CI=1,06-13,537). Ibu rumah tangga yang telah melakukan VCT 3,79 kali lebih cenderung untuk melakukan upaya pencegahan HIV/AIDS baik dibandingkan yang tidak melakukan VCT. Kesimpulan: Pemberian edukasi dan pemeriksaan VCT dapat memberikan perilaku pencegahan HIV yang lebih baik pada ibu rumah tangga. Faktor riwayat VCT dan keterpaparan informasi berperan dalam perilaku pencegahan HIV pada ibu rumah tangga. Kata kunci: HIV/AIDS, kesehatan reproduksi, VCT